Resposta do capim-elefante a doses de nitrogênio e de fósforo em condições de campo - Oliveira, Luiz Eduardo Cordeiro de (2018)
Elephant grass (Pennisetum purpureum Schum) stands out for its high dry matter (DM) production per unit area and for its good nutritional value, being cultivated all over Brazil. For the maintenance of high yields of DM, it is indispensable the proper management of nutrients, mainly nitrogen (N), in view of the low levels of this nutrient in the soil in relation to the plant need. After N, phosphorus (P) is the nutrient that generally limits the productivity of forage crops, because of the low levels of this nutrient available in tropical soils. The objective of this work was to evaluate the productivity of elephantgrass (Cameroon cv.) Fertilized with N and P applied in different doses. The field experiment was installed in an area of the Agricultural School of Jundiaí, belonging to the Federal University of Rio Grande do Norte, in Macaíba-RN. The experimental design was a randomized block with eleven treatments and four replicates. The treatments consisted of five doses of nitrogen (0, 200, 400, 600 and 800 kg ha-1 of N) and five doses of phosphorus (0, 50, 100, 150 and 200 kg ha-1 of P2O5), plus a control treatment without the application of N and of P. In all eleven treatments 150 kg ha-1 of K2O, 30 kg ha-1 of S and 3.0 kg ha-1 of Zn were applied. 150 kg ha-1 of P2O5 was applied in treatments for N doses, while 600 kg ha-1 of N was applied in the treatments for P doses. The experimental area was 540 m² (15 x 36m), with four spaced blocks of 1.0 m, each block containing 11 plots, there being no spacing between plots in the same block. Each experimental plot measured 2.8 m wide by 3.0 m in length, and contained four elephant grass planting lines spaced 0.7 m. The average area of the plot 4.2 m2, consisting of the two central lines. The evaluated variables were: plant height, stem diameter, dry matter yield of the aerial part of the plant, N content and P content in the aerial part and amounts of N and P exported by the harvests. Variance and regression analyzes were performed, and the N and P2O5 rates associated with several dry matter productivity levels in each cut and for the accumulated productivity in the three cuts were estimated. The recommended doses of N for elephantgrass ranged from 405 to 643 kg ha-1 of N to produce 37.4 to 39.9 ha ha of accumulated dry matter in the first three cuts, respectively. For P, the recommended doses ranged from 54 to 109 kg ha-1 of P2O5, to produce 37.9 to 40.0 t ha-1 dry matter accumulated in the first three cuts, respectively